Digital Political Communication Strategy on The Victory Bertaji Couple in Oku Pilkada 2024 - Sindri Dwi Riyantri; Khomsahrial Romli; Khairullah Khairullah (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the stage of political communication strategy of Teddy Meilwansya and Marjito Bachri (BERTAJI) couple in winning the Regional Head election contestation of Ogan Komering Ulu regency, South Sumatra province in 2024. Methodology: This study uses a descriptive qualitative approach to the method of content analysis (content analysis). The object of the study focused on the official Instagram account of the couple Teddy Meilwansya and Marjito Bachri (BERTAJI) and the contents uploaded during the Ogan Komering Ulu Regency Regional Head election campaign period in 2024. Results: Tajik couples used Instagram to build a positive image, interact directly with young voters, and convey campaign messages in a consistent visual and narrative manner. Conclusions: The success of the couple Teddy Meilwansya and Marjito Bachri (BERTAJI) in winning the Ogan Komering Ulu Regency regional election in 2024 was due to the adoption of digital political communication strategies, especially through Instagram, which effectively built a positive image and facilitated participatory communication with young voters. Limitations: This study is limited to the analysis of the political communication strategy of the BERTAJI couple in the 2024 Ogan Komering Ulu Regency Election. Contributions: This research contributes significantly by showing that success in local political contestation in the digital age depends heavily on adaptive communication strategies that blend conventional and digital approaches, especially the use of social media such as Instagram as the main instrument to build image, convey vision-mission, and interact directly with young voters.